The Effect of Shaker Exercise Therapy on Dysphagia in Stroke Patients Admitted to the Intensive Care Unit (ICU) at Grandmed Hospital Lubuk Pakam - Juni Mariati Simarmata; Debi Dinha Octora; Maita Sarah; Martina Evlyn Romauli Hutahaean (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Stroke patients frequently experience dysphagia due to impairment of the glossopharyngeal, vagus, and hypoglossal nerves, which consequently reduces swallowing function. Shaker exercise has been shown to improve swallowing disorders through isometric and isokinetic training that enhances the strength of the suprahyoid muscles in the neck via upward (elevation) and forward (protrusion) movements. This study aimed to analyze the effect of Shaker exercise therapy on dysphagia in stroke patients admitted to the Intensive Care Unit (ICU) at Grandmed Hospital Lubuk Pakam. This study employed a quantitative approach with a pre-experimental design using a one-group pre-test and post-test method. A total of 11 stroke patients were recruited using a total sampling technique. Dysphagia levels were measured before and after the administration of the Shaker exercise intervention. Data analysis was conducted using the Shapiro–Wilk normality test and the Paired T-test with a significance level of 0.05. The results indicated that prior to the intervention, the majority of respondents were in the low score category (20–80), accounting for 7 individuals (63.6%), while 4 respondents (36.4%) were in the high score category (81–100). Following the intervention, all respondents (100%) were classified in the high score category (81–100), with no participants remaining in the low category. The Paired T-test revealed a p-value of 0.000 (<0.05), indicating a statistically significant difference in dysphagia conditions before and after the intervention. In conclusion, Shaker exercise is significantly effective in reducing dysphagia among stroke patients. This improvement is attributed to the strengthening of the suprahyoid muscles, which enhances the opening of the esophageal sphincter and facilitates the passage of food into the lower digestive tract.